2014
DOI: 10.1103/physrevb.89.094420
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical study of magnetic ordering and local atomic polarization in Ru-substitutedLu2Fe17

Abstract: The distribution of magnetic moments in the iron-rich intermetallic compound Lu 2 Fe 17 with Fe partly substituted by Ru has been investigated on Lu 2 Fe 16.5 Ru 0.5 by using several techniques. The crystal structure and temperature evolution of the magnetic structure was studied using high resolution and high flux neutron powder diffractometers. In contrast to the parent Lu 2 Fe 17 , which transforms on cooling from an antiferromagnetic to a ferromagnetic state, Lu 2 Fe 16.5 Ru 0.5 is an antiferromagnet (Néel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 55 publications
(71 reference statements)
0
7
0
Order By: Relevance
“…Then precipitation of the α-Fe phase emerges for the Lu 2−x Fe 17 compounds. 24 It is interesting that the characteristic peaks of (300) and (004) keep moving inversely (Figure 1d) for the 2:17 phase, indicating that the lattice parameters are distinctly tuned with decreasing Lu content. The similar tendency between the lattice parameter and dumbbell occupation reveals that an increase of the dumbbell content intimately affects the lattice parameters with the Lu content (Figure S3).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Then precipitation of the α-Fe phase emerges for the Lu 2−x Fe 17 compounds. 24 It is interesting that the characteristic peaks of (300) and (004) keep moving inversely (Figure 1d) for the 2:17 phase, indicating that the lattice parameters are distinctly tuned with decreasing Lu content. The similar tendency between the lattice parameter and dumbbell occupation reveals that an increase of the dumbbell content intimately affects the lattice parameters with the Lu content (Figure S3).…”
mentioning
confidence: 94%
“…This suggests that the disorder substitutions of dumbbells gradually approach the saturation of solid solubility. Then precipitation of the α-Fe phase emerges for the Lu 2– x Fe 17 compounds . It is interesting that the characteristic peaks of (300) and (004) keep moving inversely (Figure d) for the 2:17 phase, indicating that the lattice parameters are distinctly tuned with decreasing Lu content.…”
mentioning
confidence: 95%
“…In Figure S1, the SEM–EDS linear sweep pattern of the Lu 1.7 Fe 17 compound indicated that the two phases are separate and the α–Fe is embedded in the matrix of the 2:17 phase. The ideal Th 2 Ni 17 -type R 2 Fe 17 compounds are derived from the CaCu 5 -type structure R Fe 5 (space group: P 6/ mmm ) with pairs of Fe atoms (denoted as dumbbells) sequentially substituting R atoms on the triple screw axis along the c axis (Figure c) . Unfortunately, the refinements of SXRD patterns indicate that there exist varying extents of lattice distortions in Y 1.7−δ Lu δ Fe 17 resulting from the partially disordered substitutions of the dumbbells (Figure d).…”
mentioning
confidence: 99%
“…R 2 Fe 17 (R = Ce [20] and Lu [21]). The temperatures of magnetic phase transitions and the magnetic structures are extremely sensitive to the interstitial impurity atoms (hydrogen, in particular) [22,23], to substitutional atoms [24] and high pressure [25]. The magnetic phase diagrams of such compositions have been obtained and studied extensively in literature [26].…”
Section: Resultsmentioning
confidence: 99%